Hybrid Event-Triggered Group Consensus Control for Heterogeneous Multiagent Systems With TVNUD Faults and Stochastic FDI Attacks - Guo, Xiang-Gui; Liu, Pei-Ming; Wu, Zheng-Guang; Zhang, Dan; Ahn, Choon Ki (IEEE transactions on automatic control, 2023)
This article investigates the group consensus of heterogeneous multiagent systems (MASs) with time-varying unknown nonidentical direction (TVUND) faults under stochastic false data injection (FDI) attacks. A fault-tolerant mechanism based on the Nussbaum function method that does not require the upper and lower bounds of the fault scaling factors nor fault directions is proposed. To bypass the challenges resulting from the summation of multiple Nussbaum functions, a group of new Nussbaum functions is developed. Meanwhile, a hybrid event-triggered mechanism (ETM) with both adaptive and memory characteristics is designed to reduce the communication burden by adjusting the trigger threshold according to not only the consensus error but also the motion trajectory of the agent itself. Finally, the simulation results illustrate the validity and merit of the designed controller.